BORDERS AT THE MARGINS: LIVED EXPERIENCES AND GOVERNANCE CHALLENGES OF BORDER COMMUNITIES IN JAMMU AND KASHMIR - Khan, Samim Ahmad; Shameem, Anjum Ara (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study re-envisions border studies by focussing on the lived experiences of communities in Jammu and Kashmir’s border regions, where borders transcend mere geopolitical lines and become vibrant socio-cultural landscapes. This research paper highlights the complex issues these communities face, such as security threats, economic exclusion, and restricted access to essential services like education and healthcare. These challenges are intensified by the region’s geographic isolation, intermittent military conflicts, and political volatility, which create an environment marked by instability and vulnerability. By examining historical conflicts, systemic neglect, and geopolitical tensions, the study reveals how these factors compound the hardships of border populations. Furthermore, this paper evaluates the effects of leadership measures, such as construction projects, health, schooling, and living characteristics in enhancing conditions in such deprived regions. Consequently, the analysis presented in the research contributes to the existing body of knowledge on effective and efficient policy implementation and governance in borderland regions, while questioning the dominant paradigms of development. Thus, this work contributes to the existing literature on border studies by providing a systematic understanding of borders, community resilience, and governance in their complex interrelationships.